Prognostic value of vasodilator stress perfusion CMR in patients with previous coronary artery bypass graft (CABG). (25th November 2020) - Pezel, T; Kinnel, M; Sanguineti, F; Garot, P; Hovasse, T; Landon, V; Unterseeh, T; Champagne, S; Louvard, Y; Morice, M.C; Garot, J
Abstract: Background: The accuracy and prognostic value of stress perfusion cardiac magnetic resonance (CMR) are well established in patients with suspected or proven coronary artery disease (CAD). Because myocardial contrast kinetics may be altered in patients with previous coronary artery bypass graft (CABG), most studies have excluded those patients in whom prognostic data are missing. Purpose: To assess the safety and prognostic value of vasodilator stress perfusion CMR in patients with previous CABG. Material: Between 2008 and 2018, we prospectively included consecutive patients with CABG referred for vasodilator stress perfusion CMR with dipyridamole. They were followed for the occurrence of major adverse cardiovascular events (MACE) defined by cardiovascular death, nonfatal myocardial infarction or late coronary revascularization (>90 days after CMR). The safety of the stress perfusion CMR was assessed by clinical monitoring for 1 hour after the end of the CMR. Univariable and multivariable Cox regressions were performed to determine the prognostic association of inducible ischemia and late gadolinium enhancement (LGE) on CMR. Results: Of 866 CABG patients (70±9 years, 89% men), 852 (98%) completed the CMR protocol and 771 (89%) completed the follow-up (median 4.2±2.7 years). Reasons for failure to complete CMR included renal failure (n=4), intolerance to stress agent (n=4), claustrophobia (n=2), poor gating (n=2) and declining participation (n=2). Stress CMR was well tolerated without occurrence of death or severe adverse event. In this cohort, 531 (61%) patients had a myocardial infarction defined by the presence of LGE with ischemic patterns in CMR. Patients without inducible ischemia or LGE experienced a substantially lower annual event rate of MACE (12.8%) than those with ischemia and without LGE (27.6%), or those with both ischemia and LGE (28.2%; p<0.001 for all). Using Kaplan-Meier analyses, the presence of myocardial ischemia was correlated with the occurrence of MACE and cardiac mortality (both p<0.0001) (Figure). In multivariable stepwise Cox regression, the absence of inducible ischemia was an independent predictor of a lower incidence of MACE (HR 2.17, 95% CI 1.56–3.13; p<0.001) and cardiovascular mortality (HR 2.38; 95% CI 1.39 0.25–4.03; p=0.001). Conclusions: Stress CMR is feasible, safe and has a good discriminative prognostic value to predict the occurrence of MACE and cardiovascular mortality in patients with CABG. Funding Acknowledgement: Type of funding source: None